Operation of DC Motor with Multi-Level Inverter in PWAM Method - Can, Erol (TECCIENCIA, 2021)
DC motor control with switching methods is an interesting devise with many practical applications. A DC-DC buck-boost converter is one of the methods used to operate the DC motor. Although the-DC buck-boost converter for dc motor applications has been widely studied, they have some handicaps. In this study, the multi-level inverter structure that is different from the methods of DC motor driving is used to drive the DC motor. There will be no passive elements in the proposed circuit although the dc-dc convert- ers have passive elements. So, while the inadequacies for the loads needing high current will be eliminated, the handicaps of the switching can be avoided. Current, torque, and voltage on the load will also be created by Pulse Width Amplitude Method (PWAM). As a different from other Pulse width modulation methods (PWM); the torque, current, and voltage of the motor can be controlled with PWAM in the horizontal and vertical axes. In the design stage; inverter switch structure and operation are given after the method of produced PWMs introduced. The equations of the voltages that will occur in the loads are created according to the working structure of the switches. DC motor structure is also given. In the simulation stage; Continuous and discontinuous modes of the proposed circuit are performed. Then torque of dc motor, armature current and speed are tested according to switching at different frequencies and different modulation indices.